Circadian rhythm of blood pressure in adolescents with obesity and arterial hypertension - Samoylyk, K. V.; Самойлик, Катерина Валеріївна (My University, 2018)
The purpose of the study was determination in children with obesity, circadian rhythm of blood pressure by means of daily monitoring of blood pressure (BP).
Keywords: тези доповідей